The difficulty of ileal transposition is offset by their results or is preferable the simplicityof tailored BAGUA? - Celik, Alper (My University, 2014)
Despite the evidence suggestive of inadequate and disappointing results with restrictive techniques like vertical banded gastroplasty (VBG) and gastric banding, why is the surgical fraternity still performing restrictive operations and trying to revise the restrictive or combination operations with further restriction? It is quite unfortunate to note the growing number of revision operations performed by bariatric and metabolic surgeons. Apparently, any restriction on humans seems to fail eventually, as observed with mechanical restrictive operations done for the surgical treatment of obesity.
La dificultad de la transposición ileal se compensa con sus resultados o es preferible la sencillez del BAGUA a medida?
Ponencia
Keywords: Diabetes; Cirugía